Thermodynamic analysis of an air solar collector. (19th September 2005) - Luminosu, Ioan; Fara, Laurentiu
The paper presents the experimental study of an air solar installation with a collecting area AC = 4.2m² and variable working fluid flow rate in the range 0.02÷0.06 kg/s. The experimental data are processed statistically through thermodynamic analysis, using energy (semi-empirical) and exergy methods. The aim of the paper is to establish the optimal air flow rate through this solar thermal system in order to ensure minimum irreversibility of the collecting-heating-cooling process under Romania's insolation conditions. The paper is also a demonstrative example of cost-effective and efficient use of solar energy for heating in Romania. It is experimentally proven that for this solar installation, the optimum air flow rate is of 0.04 kg/s. At a flow rate of 0.04 kg/s, irreversibility has the lowest values for all daytime hours with a maximum at noon (2640 W). For this flow rate the exergy efficiency reaches the highest value, ηex:max = 0:197.